Unexpected cause of fever in a patient with untreated HIV. (3rd July 2018) - Chhetri, Mamta; Miaskiewicz, Stasia; Lawrence, Taylor Abegg; Kapetanos, Anastasios
Abstract : We report a case of a 27-year-old man with a history of untreated HIV who presented with fever, rash and leg cramps. Initial suspicion was high for an infectious process; however, after an exhaustive evaluation, thyrotoxicosis was revealed as the aetiology of his symptoms. Recent intravenous contrast administration complicated his workup to determine the exact cause of hyperthyroidism. Differentiation between spontaneously resolving thyroiditis and autonomous hyperfunction was paramount in the setting of existing neutropenia and the need for judicious use of antithyroid therapy. The inability to enlist a nuclear scan in the setting of recent iodinated contrast administration prompted alternative testing, including thyroid antibodies and thyroid ultrasound. In this case, we will discuss the diagnostic challenges of thyrotoxicosis in a complex patient, the sequelae of iodine contrast administration, effects of iodine on the thyroid and the predictive value of other available tests.